A single-molecular twin rotor: correlated motion of two pyrimidine rings coordinated to copper1. Issue 14 (18th February 2015) - Takara, Yusuke; Kusamoto, Tetsuro; Masui, Tatsuya; Nishikawa, Michihiro; Kume, Shoko; Nishihara, Hiroshi
<x xml:space="preserve">Abstract</x> A single molecular twin rotor comprising a copper complex exhibits the correlation of the motions of two coordinated pyrimidine rings.